2020
DOI: 10.3390/ijms21197091
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Spodium Bonds in Zn(II) Complexes: Insights from Theory and Experiment

Abstract: Two new dinuclear zinc(II) complexes, [Zn2(µ1,3-OAc)(L1)2]I·MeOH (1) and [Zn2(µ1,3-OAc)(L2)(NCS)] (2), (where HL1 = 2-(((3-(dimethylamino)propyl)amino)methyl)-6-methoxy-phenol and H2L2 = 2,2′-[(1-Methyl-1,2-ethanediyl)bis(iminomethylene)]bis[6-ethoxyphenol]) have been synthesized and characterized by elemental and spectral analysis. Their X-ray solid state structures have been determined, revealing the existence of intramolecular Zn···O spodium bonds in both complexes due to the presence of methoxy (1) or etho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Therefore, the total contribution of the hydrogen bonds to the formation of DIMER-II is -1.20 kcal/mol, which is insignificant compared to the spodium bonding energy, which is -12.9 kcal/ mol (-6.5 kcal/mol each spodium bond). These values agree well with the recently reported energetic features of spodium bonds [80].…”
Section: Resultssupporting
confidence: 93%
“…Therefore, the total contribution of the hydrogen bonds to the formation of DIMER-II is -1.20 kcal/mol, which is insignificant compared to the spodium bonding energy, which is -12.9 kcal/ mol (-6.5 kcal/mol each spodium bond). These values agree well with the recently reported energetic features of spodium bonds [80].…”
Section: Resultssupporting
confidence: 93%
“…[22][23][24][25] Since last year, the related experimental and theoretical studies have been reported for spodium bonds rapidly. [26][27][28][29][30][31][32][33] For the planar structures such as MCl 3 À (M=Zn, Cd, Hg), a π-hole lies directly above each M atom, [26] while a σ-hole is found for it in the nonplanar molecules. [21] The spodium bond is usually present between different or same molecules [27] although intramolecular spodium bond is also described.…”
Section: Introductionmentioning
confidence: 99%
“…[21] The spodium bond is usually present between different or same molecules [27] although intramolecular spodium bond is also described. [28,29] Other than molecules with lone pairs, carbenes are also evidenced to be used as the electron donors in the spodium bonds. [30] Through the regulation of the group 12 atom and the electron donor, the spodium bond varies with strength from weak to strong.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations